1974
DOI: 10.1002/1097-0142(197408)34:2<282::aid-cncr2820340211>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal patterns of mucus secretion in apparently normal mucosa of large intestine with carcinoma

Abstract: Our previous studies have shown that histologically normal mucosa adjacent to carcinomas of the large intestine is often abnormal histochemically. This „transitional”︁ mucosa, as we termed it, is characterized by an increase of sialomucins, accompanied usually by a decrease or absence of the sulphomucins which are predominant in the normal mucosa of the large intestine. The extent and intensity of these mucin changes were not clear, and so we have mapped them by cutting strips of mucosa from the whole length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
66
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(69 citation statements)
references
References 24 publications
3
66
0
Order By: Relevance
“…It mnay be normal in haematoxylin-eosin stained sections or may show longer crypts with branching and larger goblet cells distended with mucus (Filipe and Branfoot, 1974). The histochemical changes in the composition of the goblet cell mucin consist of an increase in sialomucins as compared with the normal mucosa in which sulphomucins predominate.…”
mentioning
confidence: 98%
“…It mnay be normal in haematoxylin-eosin stained sections or may show longer crypts with branching and larger goblet cells distended with mucus (Filipe and Branfoot, 1974). The histochemical changes in the composition of the goblet cell mucin consist of an increase in sialomucins as compared with the normal mucosa in which sulphomucins predominate.…”
mentioning
confidence: 98%
“…The timing of the bypass operation in relation to azoxymethane treatment and the degree of resultant weight loss seem to be critical factors in the development of tumours Williamson, 1980) and may partly explain why colon cancer has not yet been reported after jejunoileal bypass for obesity in man. Filipe has postulated that an increase in sialomucins, which she found to correlate with the presence of epithelial dysplasia in man and the rat, might represent early malignant transformation of the colonic mucosa (Dawson & Filipe, 1976;Filipe, 1975;Filipe & Branfoot, 1974;Filipe et al, 1982). Our own findings call this hypothesis into question.…”
Section: Discussionmentioning
confidence: 74%
“…There is general agreement that the premalignant colonic epithelium of the rat shows an increased number of goblet cells containing sialomucins, and both Filipe and Shamsuddin have described a similar pattern in the "normal" colonic mucosa of patients with carcinoma of the large bowel (Dawson & Filipe, 1976;Filipe & Branfoot, 1974;. Hyperplasia of goblet cells containing sialomucin is particularly marked in the distal colon, where azoxymethane-induced carcinomas most frequently arise .…”
Section: Discussionmentioning
confidence: 90%
“…A large proportion of colonic mucins from normal human colon consists of sulphomucins, whereas in colonic tumours a marked decrease or absence of sulphomucins is accompanied by an increase in sialomucins (Filipe, 1979). However, it has also been found that normal colonic mucosa adjacent to and remote from colon carcinomas show a shift towards sialomucins (Filipe & Branfoot, 1974;Shamsuddin et al, 1981).…”
Section: Discussionmentioning
confidence: 99%